2021
DOI: 10.1108/ijebr-11-2020-0797
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Islamic boarding schools by applying the humane entrepreneurship approach: the case of Indonesia

Abstract: PurposeIslamic boarding schools are education institutions that have been developing in Indonesia as places for the Indonesian people to learn and gain knowledge in the perspectives of the Islamic religion and Indonesian nationalism. This study aims to explore the potential of Islamic boarding schools as places to support and to empower the economy and to increase the participation of students in entrepreneurial activities by applying the Humane Entrepreneurship approach. This study identifies the humane entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 38 publications
1
45
0
1
Order By: Relevance
“…However, it would be more uncomfortable if universities had to go out of business because they lost society's trust or could not compete. Informal religious events, including community gatherings, can be essential in promoting and raising awareness of Islamic entrepreneurship integrated with spiritual principles (Anggadwita et al, 2021). Fulfilling several characteristics of muslimpreneur by the leaders also shows a spiritual-religious element in the development of student entrepreneurship.…”
Section: Resultsmentioning
confidence: 99%
“…However, it would be more uncomfortable if universities had to go out of business because they lost society's trust or could not compete. Informal religious events, including community gatherings, can be essential in promoting and raising awareness of Islamic entrepreneurship integrated with spiritual principles (Anggadwita et al, 2021). Fulfilling several characteristics of muslimpreneur by the leaders also shows a spiritual-religious element in the development of student entrepreneurship.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the research results, it is found that the main problem in the classification effort is the lack of synergy, the problematic human resources and the businesses’ legality. According to Anggadwita and Dana (2021), entrepreneurship activities in pesantren are facing problems that can be divided into three aspects, which are human resources, technology and management issues. Business synergy can lead to the activities of information and technology transfers.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, pesantren is not only focusing on the development of the education system but also in the development of business units. Several pesantren are involved in those efforts as a way to prepare their santri to face the socio-economic challenges in the future (Anggadwita and Dana, 2021). Pesantren in general have not yet been integrated into their business unit and also have limited income sources, which are mainly generated from the santri .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The current forms of pesantren are the results of a very long and dynamic process. Pesantren, as the oldest educational institutions in Indonesia, has a significant contribution in the nation's struggle to educate people to become fully human ( Yasid, 2018 ; Misdar, 2017 ; Musthofa, 2015 ; Anggadwita et al., 2021 ). Its education system continues to grow and adapt to the dynamics of life is an effort to meet the demand of the times that is still in accordance with the Islamic values ( Dhofier, 2011 ; Kuntowidjojo, 1991 ; Ziemek, 1983 ).…”
Section: Introductionmentioning
confidence: 99%